A Study on Chicken Consumption Pattern and Consumer Preference for Processed Chicken in Coimbatore City - Yesodha Devi, N.; Kanchana, V. S. (Indian Journal of Marketing, 2007)
The present study seeks to examine the opinion of 200 non-vegetarians about chicken consumption pattern and their preference for processed chicken. The respondents were selected by simple random sampling in Coimbatore city of Tamilnadu. The relevant data on demographic characteristics, weekly chicken consumption, and preference for non-vegetarian items, awareness and preference for processed chicken were collected with the help of a structured questionnaire. Majority of the respondents consume chicken once in a week and purchase 1 kg of chicken weekly, mostly from nearby chicken stalls. Most of the respondents have given the top priority to the non-vegetarian item Chicken. There is awareness about processed chicken but very few purchase it because they feel processed chicken is not fresh. The chi-square analysis shows that the personal factors of the respondents does not have a significant influence on the source of purchase, source of awareness and the reasons for purchasing processed chicken while some of the personal factors have significant influence on the quantity of chicken purchased.